A cultural history of Jews in California - Zuckerman, Bruce; Deverell, William, 1962-; Ansell, Lisa (Jewish role in American life, 2009)
There are two aspects of this volume that merit special notice. First, the aim of the collection of essays and studies in this volume is intended to stress the cultural aspects of the Jewish experience of coming up to and living in the Golden State. Second, while this volume looks at the Jewish experience in California in general - nonetheless, particular emphasis is placed on Southern California, where the Casden Institute is situated. Contents: Isaias Hellman and the Creation of California (Frances Dinkelspiel); A Twice-Told Journey: Sarah Newmark in the Russian Polish Shtetl: How a Jewish California Matron Confronted Her European Heritage (Karen S. Wilson ); Postscript: The Western States Jewish History Archives (Gladys Sturman and David Epstein); From Civic Defense to Civil Rights: The Growth of Jewish American Interracial Civil Rights Activism in Los Angeles (Shana Bernstein); The Third Temple: Iranian Jews and the Blessings of Exile - A personal Memoir (Gina Nahai); Jewish Homegrown History: In the Golden State and Beyond (Marsha Kinder).